2015
DOI: 10.1103/physrevlett.115.132301
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Bulk Viscosity of QCD in Ultrarelativistic Heavy-Ion Collisions

Abstract: We investigate the consequences of a nonzero bulk viscosity coefficient on the transverse momentum spectra, azimuthal momentum anisotropy, and multiplicity of charged hadrons produced in heavy ion collisions at LHC energies. The agreement between a realistic 3D hybrid simulation and the experimentally measured data considerably improves with the addition of a bulk viscosity coefficient for strongly interacting matter. This paves the way for an eventual quantitative determination of several QCD transport coeffi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
388
4
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(415 citation statements)
references
References 77 publications
18
388
4
5
Order By: Relevance
“…In [116,117], effects from the bulk viscosity transport coefficient, ζ, were included in event-by-event hydrodynamics and state-of-the-art hydrodynamic models [101,113] have shown that this coefficient is an important ingredient in the description of heavy ion experimental data. For instance, in the calculations performed in [101] a profile for the bulk viscosity peaking at the crossover allowed for a simultaneous agreement with experimental data for different physical observables.…”
Section: Bulk Viscositymentioning
confidence: 99%
“…In [116,117], effects from the bulk viscosity transport coefficient, ζ, were included in event-by-event hydrodynamics and state-of-the-art hydrodynamic models [101,113] have shown that this coefficient is an important ingredient in the description of heavy ion experimental data. For instance, in the calculations performed in [101] a profile for the bulk viscosity peaking at the crossover allowed for a simultaneous agreement with experimental data for different physical observables.…”
Section: Bulk Viscositymentioning
confidence: 99%
“…For simplicity, e↵ects from the temperature dependence of ⌘/s in the hadronic [72][73][74] or in the QGP phase [75] are neglected here and, thus, we set ⌘/s to be a constant. Also, in this first study bulk viscosity [61,62,76] is set to zero. The initial time for all the hydrodynamic simulations was 0.6 fm and we used the lattice-based equation of state EOS S95n-v1 [77] and an isothermal Cooper-Frye [78] freezeout with freeze-out temperature T F = 120 MeV for MCKLN and T F = 130 for MCGlauber.…”
Section: Fig 1 (Color Online) Model Comparison To Cms Datamentioning
confidence: 99%
“…[5] exposes the possibility of divergence of ζ near the transition temperature. In recent times, different phenomenological investigations [6][7][8][9][10][11][12][13][14][15][16][17][18] demonstrated that bulk viscosity can have a non-negligible effect on heavy ion observables, where the values of ζ/s in Ref. [18] is assumed to be quite large.…”
Section: Introductionmentioning
confidence: 99%